Identifying wastewater management tradeoffs: Costs, nearshore water quality, and implications for marine coastal ecosystems in Kona, Hawai'i. - Christopher A Wada (Public Library of Science (PLoS), 2021)
Untreated and minimally treated wastewater discharged into the environment have the potential to adversely affect groundwater dependent ecosystems and nearshore marine health. Addressing this issue requires a systems approach that links land use and wastewater management decisions to potential impacts on the nearshore marine environment via changes in water quality and quantity. To that end, a framework was developed to assess decisions that have cascading effects across multiple elements of the ridge-to-reef system. In an application to Kona (Hawai'i, USA), eight land use and wastewater management scenarios were evaluated in terms of wastewater system upgrade costs and wastewater related nutrient loads in groundwater, which eventually discharge to nearshore waters, resulting in potential impacts to marine habitat quality. Without any upgrades of cesspools or the existing wastewater treatment plant (WWTP), discharges of nutrients are expected to increase substantially with permitted development, with potential detrimental impacts to the marine environment. Results suggest that converting all of the existing cesspools to aerobic treatment units (ATU) and upgrading the existing WWTP to R-1 quality provide the highest protection to nearshore marine habitat at a cost of $569 million in present value terms. Other wastewater management options were less effective but also less costly. For example, targeted cesspool conversion (a combination of septic and ATU installation) in conjunction with the WWTP upgrade still provided a substantial reduction in nutrients and potential impacts to marine habitat quality relative to the present situation at a price point roughly $100 million less than the entirely ATU option. Of note, results were more sensitive to the inclusion of the WWTP upgrade option than they were to assumptions regarding the efficiency of the cesspool conversion technologies. The model outputs also suggest that the spatial distribution of potential impacts should be carefully considered when comparing different wastewater management scenarios. When evaluated separately, the WWTP option reduced total nutrients by more than the targeted cesspool conversion option at a fraction of the cost. However, potential improvements in marine habitat quality only occurred in the immediate vicinity of the WWTP, whereas the benefits under targeted cesspool conversion were more evenly distributed along the coast.